Green‐wave surfing increases fat gain in a migratory ungulate. Issue 7 (22nd February 2018) - Middleton, Arthur D.; Merkle, Jerod A.; McWhirter, Douglas E.; Cook, John G.; Cook, Rachel C.; White, P. J.; Kauffman, Matthew J.
Abstract : Each spring, migratory herbivores around the world track or 'surf' green waves of newly emergent vegetation to distant summer or wet‐season ranges. This foraging tactic may help explain the great abundance of migratory herbivores on many seasonal landscapes. However, the underlying fitness benefits of this life‐history strategy remain poorly understood. A fundamental prediction of the green‐wave hypothesis is that migratory herbivores obtain fitness benefits from surfing waves of newly emergent vegetation more closely than their resident counterparts. Here we evaluate whether this behavior increases body‐fat levels – a critically important correlate of reproduction and survival for most ungulates – in elk Cervus elaphus of the Greater Yellowstone Ecosystem. Using satellite imagery and GPS tracking data, we found evidence that migrants (n = 23) indeed surfed the green wave, occupying sites 12.7 days closer to peak green‐up than residents (n = 16). Importantly, individual variation in surfing may help account for up to 6 kg of variation in autumn body‐fat levels. Our findings point to a pathway for anthropogenic changes to the green wave (e.g. climate change) or migrants' ability to surf it (e.g. development) to impact migratory populations. To explore this possibility, we evaluated potential population‐level consequences of constrained surfing with a heuristic model. If green‐wave surfing deteriorates by 5–15 days from observed, our model predicts up to a 20% decrease in pregnancy rates, a 2.5% decrease in population growth, and a 30% decrease in abundance over 50 years. By linking green‐wave surfing to fitness and illustrating potential effects on population growth, our study provides new insights into the evolution of migratory behavior and the prospects for the persistence of migratory ungulate populations in a changing world.